2021
DOI: 10.15173/ijsap.v5i1.4455
|View full text |Cite
|
Sign up to set email alerts
|

Trilateral partnership: An institution and students’ union collaborative partnership project to support underrepresented student groups

Abstract: This case study describes a staff-student partnership project from the perspective of three staff members based across independent departments within a UK higher education institution (HEI) and its students’ union. The authors, drawing upon an intersecting passion for advancing student equality, diversity, inclusion, widening participation and student engagement, developed a cross-collaborative and student-centred partnership project to create a series of guides specifically for underrepresented student groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The challenges of being a student representative are discussed in terms of training in quality assurance activities, but there is also a role and/or responsibility related to advocacy or activism through student unionism. Islam, Burnett, and Collins (2021) reported that student unions (or student guilds) are present at almost all public universities in the UK with student officers who represent the student body and have various roles, including advice.…”
Section: Learning Environment Versus Studentmentioning
confidence: 99%
“…The challenges of being a student representative are discussed in terms of training in quality assurance activities, but there is also a role and/or responsibility related to advocacy or activism through student unionism. Islam, Burnett, and Collins (2021) reported that student unions (or student guilds) are present at almost all public universities in the UK with student officers who represent the student body and have various roles, including advice.…”
Section: Learning Environment Versus Studentmentioning
confidence: 99%